The role of the Judiciary in the realization of the fundamental right to health from the Federal Constitution of 1988 (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article will address the constitutional and legal contours of the fundamental right to health, as well as the contribution made by the Judiciary in its realization. Some issues usually invoked in discussions on the subject will also be highlighted, such as judicial control of public policies, the reserve of the possible and judicial activism. It will be sought to demonstrate how judicial decisions have repercussions on political decisions, in a true dialog between the Powers, each preserving its independence.
Keywords: Right to health; Public policies; Judicial activism; Reserve of the possible